CARACTERIZAÇÃO FLORÍSTICA E DINÂMICA DE FRAGMENTO DE FLORESTA ATLÂNTICA NO PARANÁ - VOGEL, Francieli; SILVA, Richeliel Albert Rodrigues; WATZLAWICK, Luciano Farinha (Brazilian Journal of Biometrics, 2019)
The aim of this study was to describe the floristic composition, horizontal structure and, diameter distribution of an Araucaria Forest fragment, located in Reserva do Iguaçu, PR, Brazil. Sampling of the trees was performed on a permanent plot of 4800 m², divided into 48 subplots of 10 m × 10 m (100 m²). The plot was installed in 2007 and repaired in 2009 and 2,012. 57 tree species were identified, distributed in 24 families and 45 genera. Shannon (H´), Simpson (C) diversity index and Pielou (J) equability index indicated that the area has a high diversity and floristic homogeneity. According to the phytosociological parameters of horizontal structure, Machaerium stipitatum Vogel, Albizia niopoides (Spruce ex Benth.) Burkart, Cupania vernalis Cambess., Diatenopteryx sorbifolia Radlk., Syagrus romanzoffiana (Cham.) Glassman and Gymnanthes klotzschiana Müll.Arg. were the most important species in the area. The annual periodic increase was 0.57 m².ha.year-1 in the first period and 0.65 m².ha.year-1 in the second one. It can be concluded that the annual mortality rate of tree individuals was higher than that of admission. Basal area results indicate that the forest is still growing to reach its full stock and, consequently, maturity.